Technological and Innovative Approaches in Developing Religious and Cultural Tourism - Kartono, Kartono; Ramadhan, Muhammad Dandi (Jurnal Toursci, 2026)
Purpose – This research aims to formulate a strategy for the development of religious and cultural tourism in Cirebon City based on technology and innovation, as an effort to answer today's challenges and maximize the existing potential in a sustainable and inclusive manner. Methods: The research was conducted using a descriptive, quantitative method. The research sample comprised 165 respondents, including visitors, individuals, and tourism-related parties. A purposive sampling approach was used. Data analysis is performed in Microsoft Excel. Result: The management of religious and cultural tourism in Cirebon City has significant potential in its history and palace heritage, but its development remains hampered by limited infrastructure, low-quality human resources (HR), and suboptimal technology adoption and integration across stakeholders. Conclusion - To optimize the potential of tourism in the digital era, it is necessary to have a sustainable tourism development strategy that must rely on technological innovation and cross-sector collaboration between the government, tourism managers, and tourism actors.